French frigate Hercule with 58 guns (engraving) - d'Ozanne (Wikimedia Commons, 1880)
Notice iconographique issue de Wikimedia Commons. Titre: French frigate Hercule with 58 guns (engraving). French frigate Hercule (Hercule) with 58 guns (engraving)
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons